Effect of Curing Temperature and Fiber on Metakaolin-based Geopolymer. (2017) - Ekaputri, Januarti Jaya; Junaedi, Subaer; Wijaya,
Abstract: This paper presents mechanical properties of geopolymer mortar with metakaolin as a base material. Cylindrical specimens were prepared with a diameter of 5 cm and 10 cm height. Four compositions of geopolymer paste varied with adding polyvinyl alcohol fiber (PVA) from 0% to 1% by volume of paste. After casting, steam curing method was conducted at 40 o C, 60 o C and 80 o C for 24 hours. A control specimen was cured at room temperature. Some tests were performed for setting time, compressive strength, split-tensile, direct-tensile and porosity. It showed that the strength of fibrous specimens was 67.29 MPa at of 56 days without steam curing. When curing temperature was risen from room temperature 80 o C, the strength increased up to 14% at 28 days. Ratio of split to compressive strength was about 10% when 1% fiber was applied. However, an optimum result was shown by specimens containing 0.6% fibers according to direct-tensile test. It is recommended to apply steam curing at 60 o C-80 o C to increase the tensile strength.